PENERAPAN MODEL TGT BERBANTUAN MEDIA KARTU PERTANYAAN UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV DI SDN SUKORAME 2 - Cahyono, Arif Tri; Ilmawati Fahmi Imron; Nurul Mubarokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Sukorame 2 Kota Kediri in the subject of Natural and Social Sciences (IPAS), specifically on the topic